2005
DOI: 10.1051/forest:2005063
|View full text |Cite
|
Sign up to set email alerts
|

Studies on European beech (Fagus sylvatica L.). Part 1: Variations of wood colour parameters

Abstract: -Colour parameters of European beech were measured using CIELab system. 103 logs from 87 trees in 9 sites were cut into boards to study the radial variations of wood colour parameters. Both site and tree effects on colour were observed. Patterns of red heartwood occurrence were defined. When excepting red heartwood there was still a highly significant effect of site and tree. Axial and radial variations were small, except very near the pith or in red heartwood, suggesting possible early selection at periphery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 5 publications
2
13
0
2
Order By: Relevance
“…2). Such values are fairly similar to those reported for beech by Liu et al (2005) and Todorović et al (2012). Contrastingly, Miklečić et al (2011) found a slightly darker color (L* = 73.9 ± 1.0).…”
Section: Colorsupporting
confidence: 80%
“…2). Such values are fairly similar to those reported for beech by Liu et al (2005) and Todorović et al (2012). Contrastingly, Miklečić et al (2011) found a slightly darker color (L* = 73.9 ± 1.0).…”
Section: Colorsupporting
confidence: 80%
“…They found significant relationships between L * and a * , but not between a * and b * . In Fagus sylvatica, Liu et al (2005) found that the parameters of the CIEL * a * b * colour system were significantly correlated (L * with a * , L * with b * , and a * with b * ), but in T. grandis the only significant correlation was with a * .…”
Section: Wood Colourmentioning
confidence: 80%
“…Wood colour, which differs widely among species as well as within a single tree (Liu et al, 2005;Nishino et al, 1998), is an important factor for determining specific uses such as furniture and decorative veneers, both very important marketing attributes (Mazet and Janin, 1990). One of the most accurate and commonly used systems for measuring wood colour is the CIELab colour system.…”
Section: Introductionmentioning
confidence: 99%
“…Wood color differs widely among species as well as within a single tree (Liu et al 2005). Pith distance is the main factor of heartwood color variation within a tree (Klumpers et al, 1993;Moya and Berrocal, 2010).…”
Section: Discussionmentioning
confidence: 99%